KAWIN SADARAH DALAM KABA SI BUYUANG KARUIK; TINJAUAN SOSIOLOGIS - Fitria Dewi (tuahtalino, 2019)
Inbreeding is a prohibited marriage because it violates religious and customary norms. This study aims to describe the factors causing the occurrence of inbreeding and the consequences of inbreeding in Kaba Si Buyuang Karuik. This study uses the method of listening and note-taking technique in collecting data, then the data are analyzed through a sociological approach with reflection theory and the content analysis methods. Based on the results of the study, there are five factors causing the incest, namely poverty, sadness, crime, love, and ignorance. The results also show that inbreeding has caused inevitable shame, unbearable sadness, and inevitable divorce.